Kecerdasan Emosional terhadap Strategi Coping pada Mahasiswa yang Bekerja - Silfiasari (Psikodinamika: Jurnal Literasi Psikologi, 2023)
Studying while working is an alternative that is often chosen by students. The pressure received by students who work is heavier than students who do not work. To deal with this pressure, a coping strategy is needed. One of the things related to coping strategies is emotional intelligence. This study aims to see the effect of emotional intelligence on working student coping strategies. The subjects in this study were 105 students at the University of Muhammadiyah Malang. The emotional intelligence instrument uses the Schutte Emotional Intelligence Scale (SEIS) by Schutte (1998) and the coping strategy instrument uses the Coping Scale by Hamby et al., (2015). Data analysis uses simple linear regression. The results of the data analysis showed that there was an influence of emotional intelligence on working student coping strategies (F = 138, p <0.001).